Portrait of Beethoven - Heintzelman, Arthur William, 1891-1965 (artist):::Creator:::::::::::: (Cedar Rapids, IA; United States of America; Torch Press)
Original etching of Beethoven by the artist. ; Note on verso: Study of young Beethoven. ; An original etching by Arthur William Heintzelman, published in an edition of two hundred copies exclusively for members of the Miniature Print Society, in care of the Torch Press, Cedar Rapids, Iowa. 1943.